2002
DOI: 10.1002/gps.632
|View full text |Cite
|
Sign up to set email alerts
|

Mental health in older adult recipients of primary care services: is depression the key issue? Identification, treatment and the general practitioner

Abstract: This study found lower levels of severe mental health problems, especially depression, than reported elsewhere, but higher prevalence of psychological distress. High levels of physical and mental health co-morbidity were found. These findings suggest that planning for primary care services needs to adopt a flexible assessment model. The development of effective, time-limited protocols and screening tools to assist the PHCT in improving their identification rates is recommended. This needs to be supported by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 59 publications
2
53
0
1
Order By: Relevance
“…16 It has been reported that distress in older patients is more difficult to detect, because elderly patients tend to show less overt symptoms of distress and often are more reluctant to talk explicitly about problems with emotional functioning. 17 Therefore, physicians need to be able to investigate those concerns explicitly by eliciting patients' disclosure and by clarifying expressed concerns. In a study of primary care involving standardized patients, the investigators reported that, in fact, physicians who recognized depression in their patients asked twice as many questions about feelings and affects compared with physicians who did not recognize depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It has been reported that distress in older patients is more difficult to detect, because elderly patients tend to show less overt symptoms of distress and often are more reluctant to talk explicitly about problems with emotional functioning. 17 Therefore, physicians need to be able to investigate those concerns explicitly by eliciting patients' disclosure and by clarifying expressed concerns. In a study of primary care involving standardized patients, the investigators reported that, in fact, physicians who recognized depression in their patients asked twice as many questions about feelings and affects compared with physicians who did not recognize depression.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of primary care involving standardized patients, the investigators reported that, in fact, physicians who recognized depression in their patients asked twice as many questions about feelings and affects compared with physicians who did not recognize depression. 17,18 In another study of general practitioners in primary care, moreover, it was found that physicians who failed to recognize their patients' distress somehow inhibited their patients' expression of verbal and vocal cues of distress. 15 Assessment skills, thus, are important for detecting patients' distress.…”
Section: Discussionmentioning
confidence: 99%
“…Precautions to be followed in averting complications of radiotherapy at hospice of head & neck cancer patients [43,44]:…”
Section: Dental Caries and Periodontitismentioning
confidence: 99%
“…This is partly complicated by their worries about stigmatization and reluctance to be referred to specialized mental health care [21]. Also, the level of agreement between targeted screening for anxiety and depression in older patients and the diagnostic findings of GPs is low [22,23]. Chronic somatic comorbidity and the absence of earlier mental problems also decreases the chance of a proper diagnosis [16][17][18]24].…”
Section: Introductionmentioning
confidence: 99%